MEDICINAL POTENTIAL OF LANTANA CAMARA: VERBENACEAE - Verma, Sunita (Journal of Drug Delivery and Therapeutics, 2018)
Lantana camara is a shrub that belongs to the family of Verbanaceae. Lantana camara is one such notorious weed which is affecting ecosystem, and causing biodiversity loss at greater extent. It is highly invasive and currently occupies a large percentage of the vegetation cover wherever it was introduced. But, Lantana camara is well known to cure several diseases and used in various folk medicinal preparations. It used in many pharmacological activities. These studies established the therapeutic potential of Lantana camara in modern medicines and a possible candidate for the drug discovery. The present review aims to document the taxonomy, ecology, morphology and medicinal properties of L. camara. Key words: Invasive, Ecology, Medicinal, Pharmacological, Weed.